Pemanfaatan Limbah Ternak sebagai Pupuk Organik untuk Membantu Meminimalisir Biaya Operasional Tanam di Desa Mrawan Kecamatan Tapen Kabupaten Bondowoso - Ninuk Indrayani; Abdullah Farhan Jennatan; Erna Dwi Lestari; Abidah Ardelia; Seny Alfina Amalia Amanda; Siti Sofia; Siti Ulfa Tri Rahayu; Nadzifa Afni Azizah; Maulidia Rahmah; Muhibah Rofahati; Muhammad Khoirul Attok; Ulfiatun Nadiroh; Fiqi Firmansha; Siti Nur Fariga Huma Khasanah; Kamilatur Rodliyah Muchlis; Dzikri Diaz Firmansyah (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This study aims to examine the use of cattle waste as organic fertilizer to minimize agricultural operational costs in Mrawan Village, Tapen District, Bondowoso Regency. Cattle waste, particularly manure, is an abundant local resource that has not been optimally utilized by the local community. The majority of farmers in the village still rely on chemical fertilizers, which are relatively expensive and have a negative impact on long-term soil health. Therefore, this program is designed to provide a sustainable alternative solution through an educational approach and community empowerment. The methods used in this activity include outreach, technical training, and direct assistance in the process of making organic fertilizer from cow manure. Education focuses on simple fermentation techniques, the composition of natural additives, and appropriate fertilizer application methods. Farmers are actively involved in every stage of the activity, so they become not only beneficiaries but also agents of change in environmentally friendly agricultural practices. The results of the activity indicate that the use of organic fertilizer from cattle waste can reduce the cost of purchasing chemical fertilizers by up to 40% in a single planting season. In addition, organic fertilizer has been shown to increase soil fertility, improve soil structure, and support healthier plant growth. Environmental impacts are also reduced, as livestock waste management is more controlled and does not pollute water or air sources. Therefore, utilizing cattle waste as organic fertilizer not only reduces environmental pollution but also provides an economic and ecological solution that benefits local farmers. This program is expected to become a model for empowerment that can be replicated in other areas with similar characteristics.